WHEN WARMTH MATTERS MORE THAN EXPERTISE: THE ROLE OF STREAMER INTERACTION IN TRUST, SOCIAL PRESENCE, AND PURCHASE INTENTION IN INDONESIAN LIVESTREAM COMMERCE - Eilin Marcelita Weyna; Ovilya Nosavan Dini; Sally Salim; Adilla Anggraeni (Jurnal Manajemen Pemasaran, 2026)
The rapid expansion of livestream commerce in Indonesia has intensified competition among streamers, making interaction quality and personal attributes critical determinants of consumers' purchase intentions. This study examines the effects of real-time interaction (responsiveness and interactivity) and streamer characteristics (attractiveness and expertise) on purchase intention, with trust and social presence serving as mediating variables. A quantitative research design was employed using an online survey of 300 Indonesian consumers with prior experience watching livestream shopping sessions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships within the Stimulus-Organism-Response framework. The findings indicate that responsiveness, interactivity, and streamer attractiveness significantly enhance trust and social presence, which in turn increase purchase intention. Streamer expertise directly influences purchase intention and social presence, but does not significantly influence trust. These results suggest that relational and interactional cues play a more prominent role than competence-based cues in shaping consumer responses during livestream shopping. The study contributes to the literature on trust formation in interactive digital environments and provides practical insights for optimizing livestream engagement and conversion strategies.